John Berkeley James Wells—An appreciation of his contributions to harpacticoid diversity and systematics - Huys, Rony (Zootaxa, 2021)
John Wells was born in Hammersmith, a district in west London, where he spent most of his childhood and teenage life. It was a surprise to find out only recently that he had received a scholarship to Latymer Upper School on King Street which is literally one block away from where I used to live when I started working at the Natural History Museum in the early 1990s. The site has a long history and can be traced to a charity school founded in 1624 by the English merchant Edward Latymer, a wealthy lawyer and puritan, who left part of his wealth for the clothing and education of “eight poore boyes” from Hammersmith.